2010
DOI: 10.1377/hlthaff.2008.0567
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Ownership Of Ambulatory Surgery Centers Linked To Higher Volume Of Surgeries

Abstract: Many physicians confronting declining reimbursement from insurers have invested in ambulatory surgery centers, where they perform outpatient surgical and diagnostic procedures. An ownership stake entitles physicians to a share of the facility's profits from self-referrals. This arrangement can create a potential conflict of interest between physicians' financial incentives and patients' clinical needs. Our analysis of Florida data for five common procedures revealed a significant association between physician-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 18 publications
1
86
2
Order By: Relevance
“…They find, however, that profitability is only one of many factors that affect surgery location decisions, with patient health and procedure complexity being potentially more important. 3 Most recently, Hollingsworth et al (2010) used Florida data to show that physicians with an ownership stake in an ASC performed significantly more surgeries than other physicians. The authors pointed to financial incentives as a possible explanation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They find, however, that profitability is only one of many factors that affect surgery location decisions, with patient health and procedure complexity being potentially more important. 3 Most recently, Hollingsworth et al (2010) used Florida data to show that physicians with an ownership stake in an ASC performed significantly more surgeries than other physicians. The authors pointed to financial incentives as a possible explanation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies often proxy financial interests by defining physician owners as those who refer above a minimum threshold of their patients to an ASC or a physician-owned entity (e.g. Hollingsworth et al, 2010;Mitchell, 2005;Gabel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research on physician ownership of surgery centers (Hollenbeck et al 2010;Hollingsworth et al 2010a;2010b;Mitchell 2010), cardiac hospitals (Barro et al 2006;Mitchell 2005;2008, Nallamothu et al 2007), imaging centers (Baker 2010;Shreibati and Baker 2012) and pharmacy services (Iizuka 2007;2012) has generally confirmed the hypothesis that ownership is associated with increased use of health care services. A limitation of most of these studies is that, in the absence of a benchmark for the optimal level of use, it is impossible to assess the impact of alternative practice arrangements on consumer welfare.…”
Section: Introductionmentioning
confidence: 93%
“…Before 2002, several small randomized trials of debridement (Merchan et al 1993) and lavage (Ike et al 1992) found that these therapies reduced knee pain. Knee arthroscopy was a well-accepted, Hollingsworth et al (2010a) to distinguish between owners and non-owners. The data include surgeon identifiers, but these cannot be linked over time, hence our focus on facility-level analyses.…”
Section: Assumptionmentioning
confidence: 99%